ANALISIS RISIKO KESEHATAN LINGKUNGAN KANDUNGAN KADMIUM (Cd) DALAM IKAN BANDENG DI KAWASAN TAMBAK LOROK SEMARANG - Angelina, Maria Sylvia; Darundiati, Yusniar Hanani; Dangiran, Hanan Lanang (Jurnal Kesehatan Masyarakat (e-Journal), 2017)
Tambak Lorok area is an area around the waters of Tanjung Mas and widely used to embank fish. The abundance of industry and the existence of the harbor caused the polluted waters of cadmium metal. The community always eat milkfish from Tambak Lorok this would pose a risk of health problems. The purpose of this study was to analyze the non-carcinogenic health risk of cadmium contained in milkfish consumed by the people in Tambak Lorok. The type of this study is observational with Environmental Health Risk Assessment (EHRA) approach. The sample in this research are 65 housewives who consumed milkfish from Tambak Lorok area. The results of this research showed that the concentration of cadmium in pond water is < 0,001 mg/L and cadmium concentration in milkfish is 0,01 mg/kg. The averageÂ  body weight of respondents is 59.8, the average intake rate is 276 gr/day, the average frequency of exposureÂ  is 92.8 days/year, and the average duration of exposure was 23.45 years. The average realtime intake result is 0,0000105 mg/kg/day; 0,0000129 mg/kg/day for lifetime for 30 years; 0,0000215 mg/kg/day for lifetime for 50 years; and 0,0000302 mg/kg/day for lifetime for 70 years. The average RQ at realtime exposure was 0.01056, for 30 years lifetime exposure is 0.01296, for 50 years lifetime exposure is 0.02159, andfor 70 years lifetime exposure is 0,0302. The conclusion is that milkfish in Tambak Lorok area safety consumed until 70 years to go and housewives asrespondent have categories not yet risk of non carcinogenic health by exposure of cadmium through ingestion path to milkfish.